The Relationship Between the Intellectual Capital Disclosure and Cost of Debt Capital – A Case of Slovenian Private Audited Organisations - Stropnik, Neca; Korošec, Bojana; Tominc, Polona (Naše gospodarstvo/Our economy, 2017)
The existing empirical research into the association between intellectual capital disclosures by organisations and the cost of debt is scarce or is based solely on the samples of the (large) listed organisations. Since agency issues between management/owners and lenders exist also in (large) private organisations whose financing is greatly dependent on loans and whose audited annual reports can be a source of additional information for external users, we performed an empirical research to find the answer to the question whether the level of intellectual capital disclosure (as a whole and of its sub-categories) of organisations is associated with the cost of their debt capital. Our study was performed on a sample of private Slovenian organisations with audited annual reports. The results of our research did not reveal that lenders would take into account intellectual capital disclosures by Slovenian private audited organisations as the information about the potential for their future cash flows when deciding on the cost of debt issued to these organisations.